2010
DOI: 10.7150/jca.1.27
|View full text |Cite
|
Sign up to set email alerts
|

Ovarian Cancer Metastatic to the Breast Presenting as Inflammatory Breast Cancer: A Case Report and Literature Review

Abstract: Background. Primary ovarian carcinoma with metastasis to the breast is rare, with only 39 cases reported in the current literature. Ovarian metastasis to the breast presenting as inflammatory breast carcinoma is even more infrequent, with only 6 cases reported.Case. We present a patient who developed metastatic inflammatory cancer of the breast from a stage IIIC papillary serous ovarian adenocarcinoma approximately 1 year after the original diagnosis. Pathologic analysis confirmed the origin of the tumor: a hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
75
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(76 citation statements)
references
References 10 publications
(20 reference statements)
1
75
0
Order By: Relevance
“…5 Less well recognised is a metastasis to breast tissue from peritoneal origin, as in our case. Diagnostic difficulties can arise in the poorly differentiated nature of peritoneal and ovarian carcinomas and this case highlights that close clinicopathological correlation is required when tissue is analysed and patients have undergone treatment for other cancers.…”
Section: Discussionmentioning
confidence: 90%
“…5 Less well recognised is a metastasis to breast tissue from peritoneal origin, as in our case. Diagnostic difficulties can arise in the poorly differentiated nature of peritoneal and ovarian carcinomas and this case highlights that close clinicopathological correlation is required when tissue is analysed and patients have undergone treatment for other cancers.…”
Section: Discussionmentioning
confidence: 90%
“…Frequently, imaging studies demonstrate metastatic lesions to the breast as dense, circumscribed and noncalcified masses. However, as a function of the presence of psamomatous bodies associated with some ovarian tumors, microcalcifications may be seen in cases of ovarian metastasis to the breast (1) . But such a differentiation may be difficult, considering that metastases to the breast generally do not present specific imaging features (6) .…”
Section: Discussionmentioning
confidence: 99%
“…According to some studies in the literature, the survival time of patients with breast metastasis from ovarian carcinoma is most of times less than one year (1) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is relatively soft in AM, with the surrounding tissue adhesion, and good activity. In addition, some literatures [3] reported that ovarian cancer and other breast metastases also presented clinical performance of IBC. Lingcheng Wang [4] reported that the clinical manifestations of bilateral breast swelling, orange dermoid change, with axillary lymph node enlargement caused by hydatidiform mole may be misrecognized as IBC.…”
Section: Diagnosis and Treatmentmentioning
confidence: 99%